1979
DOI: 10.1177/000456327901600181
|View full text |Cite
|
Sign up to set email alerts
|

Serum Antioxidant Activity in Normal and Abnormal Subjects

Abstract: SUMMARY Serum antioxidant activity (ADA) was correlated with the serum caeruloplasmin and serum copper concentration and with the total and available serum iron-binding capacity in 313 normal and abnormal subjects. In all groups except in patients with Wilson's disease (hepatolenticular degeneration) there was a highly significant direct correlation between serum ADA and serum caeruloplasmin concentration. A statistically significant direct correlation between serum ADA and the available iron-binding capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
2

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(23 citation statements)
references
References 13 publications
1
19
2
Order By: Relevance
“…These results suggest that the direct action of 02 is not responsible for the cell injuries in the present experiments. Cranfield (1979) reported that the antioxidant activity was partly related to iron free Tf as well as Cp, but in the present experiment pregnant, normal, and inflammatory sera in this order of concentration contained iron free Tf independently of antioxidant activity. Serum Fe was, however, inversely related to the number of viable cells.…”
Section: Discussioncontrasting
confidence: 67%
“…These results suggest that the direct action of 02 is not responsible for the cell injuries in the present experiments. Cranfield (1979) reported that the antioxidant activity was partly related to iron free Tf as well as Cp, but in the present experiment pregnant, normal, and inflammatory sera in this order of concentration contained iron free Tf independently of antioxidant activity. Serum Fe was, however, inversely related to the number of viable cells.…”
Section: Discussioncontrasting
confidence: 67%
“…In addition to known scavengers protecting against celluar injury by oxygen free radicals [1][2][3], the presence of a potent AOA in serum was revealed by Dormandy [I, 22], Stocks et al [16] and Caranfield et al [23]. We deter mined the serum AOA in CRF patients using fresh ox brain homogenate according to the method of Stocks et al [16].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of lipid peroxides increase significantly in the maternal circulation when a women becomes pregnant [5][6][7][8]. However, various antioxidants, such as vitamin E, ceruloplasmin, erythrocyte thiols [6] and iron-binding capacity [12,13] also increase. Several of these increase progressively with advancing gestation [14,15], while serum iron concentrations progressively decrease.…”
Section: Pregnancy and Oxidative Stressmentioning
confidence: 99%